2014
DOI: 10.1111/cea.12281
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors governing indoor fungal diversity and risk of asthma

Abstract: Exposure to dampness and fungi in the home is a known risk factor for individuals with allergic asthma. Inadequate heating and ventilation may lead to dampness and concomitant increased exposure to spores of allergenic fungi such as Aspergillus and Penicillium. These fungi have been cultured from sputum of asthmatic and non-asthmatic individuals, and implicated in the initiation or exacerbation of asthma. Indoor environmental factors influence the presence and concentrations of fungal propagules and, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 72 publications
3
53
0
Order By: Relevance
“…5,8,9,32 Dampness in the indoor environment is a major risk factor for the proliferation of fungi on a variety of building materials and can result in high concentrations of fungal bioaerosols within the indoor environment. 5,10,33 To date, limited research has been conducted to investigate the role of an evaporative cooler, a system utilizing water vapor to cool the indoor environment, on the proliferation of fungi and indoor air quality (IAQ) within these environments. In this study, fungal populations were detected for the first time in homes cooled with either AC or EC systems using molecular-based approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,9,32 Dampness in the indoor environment is a major risk factor for the proliferation of fungi on a variety of building materials and can result in high concentrations of fungal bioaerosols within the indoor environment. 5,10,33 To date, limited research has been conducted to investigate the role of an evaporative cooler, a system utilizing water vapor to cool the indoor environment, on the proliferation of fungi and indoor air quality (IAQ) within these environments. In this study, fungal populations were detected for the first time in homes cooled with either AC or EC systems using molecular-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,9 Several factors contribute to the propagation of fungal contaminants in indoor environments, including dampness and humidity. 10 Occupants are often unaware that such conditions can result in or exacerbate existing health effects. It has been observed that most people spend almost 90% of their time indoors.…”
Section: Introductionmentioning
confidence: 99%
“…18 The abundance of Aspergillus and Penicillium spores in the indoor environment may be explained by the finding that although optimal fungal growth requires high humidity, some xerophilic species of the genera Aspergillus and Penicillium are able to survive in a dry environment. 14,19 Prevalence of fungal sensitization…”
Section: Indoor Environmental Fungimentioning
confidence: 99%
“…102 Therefore, housing intervention may be necessary for the management of fungal allergen-sensitized severe asthma. 14 Numerous allergens from Aspergillus have been identified and approved by the WHOeIUIS Allergen Nomenclature Subcommittee ( Table 4). Some of these allergen components are species-or genus-specific, while others are pan-allergens that display cross-reactivity beyond the family or order.…”
Section: Aspergillusmentioning
confidence: 99%
“…Ethical approval for this cross sectional study was granted by the University of Exeter worldwide public health concern because of its association with an increased risk of 76 allergic diseases (Fisk et al, 2007;, now elevated concentrations of spores and hyphal fragments (Sharpe et al, 2014c), 80 which in turn is influenced by the type of material (Andersen et al, 2011), moisture 81 (Flannigan et al, 2011), indoor air velocity, and the types of fungi present (Mensah-…”
mentioning
confidence: 99%